Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Discover comprehensive solutions to your questions from a wide network of experts on our user-friendly platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

(x^-2/y^-3)^2 / (y/x^2)^-3

Sagot :

[tex] \frac{ (\frac{ x^{-2} }{ y^{-3} })^2 }{ (\frac{y}{ x^{2} })^{-3} } = \frac{ (\frac{ x^{-4} }{ y^{-6} }) }{ (\frac{ y^{-3} }{ x^{-6} }) }= \frac{ x^{-4}* x^{-6} }{ y^{-3}* y^{-6} } = \frac{ x^{-10} }{ y^{-9} } [/tex]
(x-²/ y-³)² = (x-²/y-³)(x-²/y-³) = (y/ x²)(y/ x²) = (y²/ x^4) = y² · x^4  =      1     
(y/ x²)-³           (y/x²)(y/x²)       (x²/y³)(x²/y³)    (x^4/ y^6)  x^4 · y^6    y^4